Pollution as a Product of Human Greediness From Nature Over Exploitation in Two Contemporary Poems Warned by Sylvia Stults (2015), and Our Mother Earth by Joshua Isham (2008) - Galuh Chaniago Putra; Leni Marlina (Universitas Negeri Padang, 2023)
This research is an analysis of two contemporary poems, Warned (Stults, 2015), and Our Mother Earth (Isham, 2008). This analysis aims to reveal human greed which leads to the destruction of nature from nature overexploitation in two contemporary poems. This analysis aims to reveal the issue of human greed towards excessive exploitation of nature which leads to the destruction of nature in the three contemporary poems. This analysis looks at human greed which is shown through the point of view of poetry. This analysis mainly uses the eco-criticism concept proposed by Cheryll Glotfelty and is also supported by other eco-criticisms. The use of the concept is based on the interpretation of the text and the context of the poem. This analysis also uses many poetry fiction tools to help the writer analyze the text. The results show that human greed still dominates the results of the destruction of nature and the low awareness of mankind to realize that they need to help the world for a better future.